Entropy-Driven Molecular Beacon Assisted Special RCA Assay with Enhanced Sensitivity for Room Temperature DNA Biosensing - Shurui Tao; Yi Long; Guozhen Liu (Biosensors)
The Phi29 DNA polymerase is renowned for its processivity in synthesizing single-stranded DNA amplicons by rolling around a circularized DNA template. However, DNA synthesis rolling circle amplification (RCA) is significantly hindered by the secondary structure in the circular template. To overcome this limitation, an engineered circular template without secondary structure could be utilized to improve the sensitivity of RCA-based assays without increasing its complexity. We herein proposed an entropy-driven special RCA technology for the detection of HPV16 E7 gene at room temperature. The strategy is composed of a molecular beacon containing a loop region for nucleic acid target recognition and a stem region to initiate RCA. With the target analyte, the stem region of the molecular beacon will be exposed and then hybridized with a special circular template to initiate the DNA amplification. We tested different designs of the molecular beacon sequence and optimized the assay’s working conditions. The assay achieved a sensitivity of 1 pM in 40 min at room temperature. The sensitivity of this assay, at 1 pm, is about a hundred-fold greater than that of conventional linear RCA performed in solution. Our proposed sensor can be easily reprogrammed for detecting various nucleic acid markers by altering the molecular beacon’s loop. Its simplicity, rapid assay time, and low cost make it superior to RCA sensors that utilize similar strategies.